2004
DOI: 10.1021/ma0496697
|View full text |Cite
|
Sign up to set email alerts
|

Concentration- and pH-Dependent Conformational Changes and Aggregation of Block Copolymers of Poly(methacrylic acid) and Poly(dimethylsiloxane) in Aqueous Media, Based on Fluorescence Spectra of Pyrene and Potentiometry

Abstract: Block copolymers of poly(dimethylsiloxane) and poly(methacrylic acid) (PDMS-b-PMA) with different molar ratios and lengths of the hydrophobic PDMS and hydrophilic PMA blocks were synthesized by radical polymerization of methacrylic acid (MA) in the presence of siloxane macroazoinitiators. Conformational changes and aggregation of the copolymers were examined by fluorescence spectroscopy of pyrene (P) as a probe and by potentiometric measurements. Fluorescence spectra were measured as a function of polymer conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…The investigators concluded that in these dilute aqueous solutions of triblocks that differ so significantly in intermolecular interactions, the concentration of the polymer played a major role in globular domain formation. In spite of working with concentrations that were lower than C* (the critical chain overlap concentration), interchain aggregation leading to hydrophilic assembly formation seems to explain the results best [29].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The investigators concluded that in these dilute aqueous solutions of triblocks that differ so significantly in intermolecular interactions, the concentration of the polymer played a major role in globular domain formation. In spite of working with concentrations that were lower than C* (the critical chain overlap concentration), interchain aggregation leading to hydrophilic assembly formation seems to explain the results best [29].…”
Section: Discussionmentioning
confidence: 93%
“…Other investigators have recently looked at dilute solution properties of poly(methacrylic acid) and PDMS block copolymers of various block molecular weights [29]. These ABA systems have hydrophobic/hydrophilic pairings as do our materials.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, spherical aggregates are formed from self-assembly of the insoluble blocks into micelle-type structures consisting of a hydrophobic core surrounded by a shell or corona of solvated blocks. The sensitivity of the fluorescence spectrum of pyrene to its environment [63,64] has been exploited to determine [158,159,171,174,176,178,179] the critical micelle concentration (CMC) following aggregation of the block copolymer chains: at low concentrations, only molecularly dissolved chains (unimers) are present which are unable to solubilize pyrene. The use of luminescence spectroscopy has featured prominently in the study of block copolymer micelles: for a representative sample of this extensive literature see, for example, references [71, and references therein.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Dependent on the constituent components within the block, stimuli responsive micelles can be formed which are critically dependent on pH and salt content. The vibrational fine structure of the emission spectrum of pyrene has also been used to probe the behavior of micelles formed in a variety of diblock copolymer systems in response to changes in the pH [166,173,174] and salt content [158,174]. Valuable information concerning the nature and stability of block copolymer micelles has been derived from fluorescence spectroscopic techniques such as excimer formation [162,163], energy transfer [164,168,169,172,175], and TRAMs [161,165,180].…”
Section: Block Copolymersmentioning
confidence: 99%
“…From the fluorescence spectra of pyrene it is possible to assess the local polarity in the probe neighborhood based on the intensity ratio of the first to the third vibronic bands (I 1 /I 3 , referred to a polarity index); higher or lower values of this index are associated with polar or nonpolar environments of the probe, respectively [26]. The excimer formation depends on the proximity and mobility of the probe and provides a reliable method for monitoring local chain conformations in a given system [27].…”
Section: Fluorescence and Surface Tensionmentioning
confidence: 99%